Role of antituberculous therapy in Eales disease - M., Periyanayagi; M., Arthi; M., Rajakumari (International Journal of Medical Research and Review, 2017)
Aim: To establish the role of Anti Tuberculous therapy (ATT) in Eales disease. Methods: This is a prospective study in which 15 patients with Eales disease of the age group 18- 40 years were included. This study was conducted from January 2014 to June 2016. In our study, all patients were previously treated with a full course of steroids and four patients were treated with Pan retinal photocoagulation for neovascularisation in addition to the steroid therapy but had recurrences of inflammation. All the above patients were treated with Category 1 Anti Tuberculous therapy and oral prednisolone in tapering doses. The patients were reviewed at 1 and 6 months while on ATT and for every 2 months for one year after completion of ATT. The presence or absence of active inflammation was assessed and the outcome was analyzed. Results: In our study, 11 patients had complete resolution of inflammation with ATT and showed no recurrence of inflammation during the follow up period of one year. Two patients developed neovascularisation and Pan retinal photocoagulation was given and was considered as non response to treatment. One patient developed vitreous hemorrhage. One patient had persistent inflammation and showed no resolution of inflammation while on ATT. Conclusion: With the above study we conclude that anti tuberculous therapy should be considered in patients with Eales disease with recurrent inflammation for preventing further recurrences and reducing ocular morbidity due to complications.